Therapeutic efficacy of 166Holmium siloxane in microbrachytherapy of induced glioblastoma in minipig tumor model - Khoshnevis, Mehrdad; Brown, Richard; Belluco, Sara; Zahi, Ilyes; Maciocco, Luca; Bonnefont-Rebeix, Catherine; Pillet-Michelland, Elodie; Tranel, Jonathan; Roger, Thierry; Nennig, Christophe; Oudoire, Patrick; Marcon, Lionel; et al. (Frontiers in Oncology, 2022)
Glioblastoma is considered the most common malignant primary tumor of central nervous system. In spite of the current standard and multimodal treatment, the prognosis of glioblastoma is poor. For this reason, new therapeutic approaches need to be developed to improve the survival time of the glioblastoma patient. In this study, we performed a preclinical experiment to evaluate therapeutic efficacy of 166Ho microparticle suspension administered by microbrachytherapy on a minipig glioblastoma model. Twelve minipigs were divided in 3 groups. Minipigs had injections into the tumor, containing microparticle suspensions of either 166Ho (group 1; n = 6) or 165Ho (group 2; n = 3) and control group (group 3; n = 3). The survival time from treatment to euthanasia was 66 days with a good state of health of all minipigs in group 1. The median survival time from treatment to tumor related death were 8.6 and 7.3 days in groups 2 and control, respectively. Statistically, the prolonged life of group 1 was significantly different from the two other groups (p < 0.01), and no significant difference was observed between group 2 and control (p=0.09). Our trial on the therapeutic effect of the 166Ho microparticle demonstrated an excellent efficacy in tumor control. The histological and immunohistochemical analysis showed that the efficacy was related to a severe 166Ho induced necrosis combined with an immune response due to the presence of the radioactive microparticles inside the tumors. The absence of reflux following the injections confirms the safety of the injection device.